Anti-vibration gloves and the forearm efforts during tools operations - Cabeças, J.M. (2009)
The objective of this paper is to analyze the forearm muscular contraction levels associated to the use of anti-vibration gloves, by comparing the contraction levels with gloves and without gloves. Two different vibration tools were used in a simulated work environment: (1) A compact Duty Multi-Cutter Bosch and (2) and a Percussion Drill with a drill bit Ø20 mm. Standard operations were performed by each subject in the following materials: (1) Performing cross- sectional cuts in 80x40 mm pine section and (2) performing 20 mm diameter holes in a concrete slab 2 x 2 m, 70 mm thick. The forearm contraction level were measured by surface electromyography in four different muscles: Flexor Digitorum Superficialis (FDS), Flexor Carpi Ulnaris (FCU), Extensor Carpi Radialis Longus (ECRL) e Extensor Carpi Ulnaris (ECU). For the flexor muscles (FDS, FCU), an increase tendency in muscular contraction was observed when the operations are performed without gloves (2-5% MVE increase in the FDS and 3-9% MVE increase in the FCU). For the extensor muscles ECU a decrease tendency in muscular contraction was observed when the operations are performed without gloves (1-10% MVE decrease). Any tendency was found in the ECRL muscle. ECU was the muscle with the highest contraction level for 79% and 71% of the operators, during the operations respectively with the multi-cutter (P50= 27-30%MVE) and with the percussion drill (P50=46-55%MVE). As a final conclusion from this study, anti- vibration gloves may increase the forearm fatigue in the posterior region of the forearm (ECU muscle) during operations with the mentioned tools